Design and Fabrication of Autonomous Entertainment Mobile Robot - Ishak, Asnor Juraiza (2003)
Mobile robots are already widely used for surveillance, inspection and transportation tasks. An emerging technology with enormous potential is the entertainment mobile robot. Sony Corporation has developed a Sony dog known as Sony's Aibo that cannot speak but can chase a ball, lie down, sit and wag its tail. The robot must operate in a safe and friendly manner, avoiding obstacles and posing no risk to human in its vicinity. The scenario in Malaysia is that not many entertainment mobile robot has been developed because generally, Malaysians are content with their role as a user rather than a developer . In order to achieve the objectives of the "Vision 2020", Malaysia should produce more scientists and developers in various areas. The best and most effective way of learning and stimulating interest in entertainment robot is through contests. Therefore, Sirim Berhad and the Ministry of Education have organized the Robot Games Festival or Robofest 2002 to encourage researchers, lecturers and students to design and develop robotic systems. The main objective of this project is to design and develop an entertainment mobile robot that can place as many beach balls as possible into the cylinder tubes within 3 minutes.